Magnetic Resonance Imaging Of Bilateral Split Lateral Rectus Transposition To the Medial Globe - Chaudhuri, Zia (Graefes Arch Clin Exp Ophthalmol, 2015)
PURPOSE: Medial transposition of the split or intact lateral rectus (LR) muscle in oculomotor palsy improves extreme exotropia. We studied rectus pulley positions using high-resolution surface coil MRI before and after LR split with medial transposition surgery in a patient with bilateral oculomotor and trochlear nerve palsies. METHODS: This is a report of a 14-year girl with 90Δ exotropia due to bilateral oculomotor and trochlear nerve palsies following traumatic midbrain infarction at age 6 years. Surgery comprised longitudinal division of each LR into a superior and inferior, threading of both halves between the inferior rectus and inferior oblique inferiorly, and inferior to the superior oblique and the superior rectus superiorly, with suturing of each 10 mm posterior to the medial rectus (MR) insertion. RESULTS: Pre-operative MRI of the orbit and extraocular muscles with thin 2 mm slices revealed bilateral atrophy of all EOMs supplied by the oculomotor and trochlear nerves. Post-operative MRI at 2 months demonstrated no significant changes in rectus EOM pulley positions compared with pre-operative values. CONCLUSIONS: The LR pulley does not change position even after split LR transposition to the MR insertion, confirming the profound constraint of the connective tissue pulley system on the LR path.